2021
DOI: 10.1371/journal.pone.0256137
|View full text |Cite
|
Sign up to set email alerts
|

Fowl adenovirus strains 1/A and 11/D isolated from birds with reovirus infection

Abstract: Inclusion body hepatitis (IBH) is, in some cases, a fatal disease affecting fowl by adenovirus strains which are subdivided into 5 species (A-E). In the current study, we investigated sequences from the Loop L1 region of the hexon gene of sequences of adenovirus field stains 1/A and 11/D isolated from a poultry flock co-infected with IBH and avian reoviruses ARVs. In early 2021, an epidemiologic survey highlighted the coinfection adenoviruses with other viruses (orthoreovirus infection) as being particularly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Outbreaks of AdVs have been frequently reported worldwide, leading to huge economic losses to the poultry industry [20]. In recent years, more and more AdVs have been isolated or detected from dead, sick, or apparently healthy birds [12,[20][21][22][23]. Since 2015, new AdVs subtypes have emerged in the our poultry industry, such as serotype FAdV-2 [24], FAdV-4 [25], FAdV-7 [26], FAdV-8a [27], FAdV-8b [24], FAdV-11 [26], and DAdV-3 [7].…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of AdVs have been frequently reported worldwide, leading to huge economic losses to the poultry industry [20]. In recent years, more and more AdVs have been isolated or detected from dead, sick, or apparently healthy birds [12,[20][21][22][23]. Since 2015, new AdVs subtypes have emerged in the our poultry industry, such as serotype FAdV-2 [24], FAdV-4 [25], FAdV-7 [26], FAdV-8a [27], FAdV-8b [24], FAdV-11 [26], and DAdV-3 [7].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that infection with immunosuppressive pathogens such as infectious bursal disease virus (IBDV), chicken infectious anemia virus (CAV), reovirus, and Marek's Disease virus (MDV) can enhance the pathogenicity of FAdV and promote the clinical manifestation of FAdV infection [19][20][21][22][23][24]. Previous research has reported that co-infection could postpone the innate immune response in chickens, which subsequently induces replication without restraint in the early stage and the induction of a cytokine storm and death [23].…”
Section: Introductionmentioning
confidence: 99%
“… 4 Aggravation of disease in concurrent infections by ≥2 viral pathogens in mammalian and avian species highlights the role of decreasing host immunity. 10 A study noted that, if the flock is immunosuppressed, experimental inoculation of CoHV1 can spread either by tissue contiguity or by viremia. 18 This might be highly relevant in our case, given that all clinically affected pigeons had high viral loads of PiCV, a pathogen widely documented for its immunosuppressive role.…”
mentioning
confidence: 99%